Export market exit and firm survival: Theory and first evidence - Sanne Hiller; Philipp J. H. Schröder; Allan Sørensen (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper deploys a dynamic extension of the Melitz (2003) model to generate predictions on export market exit and firm survival in a setting where firms endogenously make exit decisions. The central driver of the model dynamics is the inclusion of exogenous economy wide technological progress. The model predicts - inter alia - that a higher relative productivity not only increases the likelihood of exporting, but also the chances of firm survival and continued export market engagements. We relate these predictions to the empirical stylized facts of export market exit and firm survival based on Danish firm-level data. We find strong evidence that firms experience a decline in market share prior to export market exit and prior to death and that the firms discontinuing their exporting activity or closing down tend to be small. Overall, our empirical results support the central predictions from the model.
Keywords: F12; F15; O33; L11; L16; 330; intra-industry trade; entry/exit; heterogeneous firms; technological change; Außenhandelswirtschaft; Intraindustrieller Handel; Marktaustritt; Unternehmenserfolg; Produktivität; Technischer Fortschritt; Allokation; Theorie; Schätzung; Dänemark